HUBUNGAN PERSONAL HYGIENE PENJAMAH MAKANAN DENGAN ANGKA KUMAN MAKANAN DI INSTALASI GIZI RSUD LUBUK SIKAPING TAHUN 2020 - Afridon Afridon; Iffa Sakina (Ensiklopedia of Journal, 2021)
Personal hygiene of food handlers in nutrition installations affects the transmission of infection through food that will be given to inpatients and outpatients. In the survey results, it was found that food handlers still did not apply hygiene in food processing, such as 79% still chatting when processing food, 47% scratching habits, 58% using jewelry, and 42% long nails. Therefore, the researcher wanted to know the relationship between personal hygiene of food handlers and the number of food germs at the Nutrition Installation of Lubuk Attitude Hospital in 2020. The type of research carried out was descriptive analytic with a cross sectional approach. In this study, total sampling was used, where the sample in this study was the same as the population, namely 19 food handlers (supervisors, waiters, and cooks) and 19 food samples at the Nutrition Installation of Lubuk Attitude Hospital carried out within a working day at the time of the study. Data analysis was carried out univariate and bivariate with Chi-Square test. From the results of the univariate analysis, it was found that personal hygiene was poor (57.9%), the number of germs in food met the requirements (73.7%), and the results of the bivariate analysis showed that there was a relationship between personal hygiene of food handlers and the number of germs in food with p = 0.045. The Head of the Nutrition Installation of Lubuk Attitude Hospital and PPI (Prevention, Control and Infection) officers must work together in increasing guidance to food handlers regarding personal hygiene in food processing.Keywords: Personal Hygiene; Number of bacteria.